Privatization of sports projects in sports institutions, clubs and federations from the point of view of administrators and sports supervisors in Sudan (Journal of the College of Basic Education, 2022)
This study aimed to identify the goals and the steps to implement the elements of the privatization of sports institutions and clubs and sports federations from the perspective of athletes Sudan projects, researchers used the descriptive analytical method for this study and the study sample consisted of (90) member of the administrative personnel of sports institutions, also used a questionnaire as a tool to gather information and also used the program spss statistical packages for data processing, and the study found the most important to the following results: -1. The most important objectives of the privatization sports institutions from the perspective of athletes in Sudan are:- Improve the quality of goods and services provided by sports facilities subject to privatization.- Efficient exploitation of economic resources for sports on the basis of the market system.- Access to modern technology through participation and attract foreign investments.- Accelerate economic growth and increase the level of economic well-being of consumers.2. Significant steps and stages of implementation of the privatization sports institutions from the perspective of athletes in Sudan are:- Establishing an independent public administration, or a team from various disciplines (Sports - economic - political - social - media - legal) under the leadership of the privatization process as a whole.- Issuing laws and regulations required for implementation.- Choosing the right time for privatization.The most important elements of the success of the programs and projects of privatization sports institutions from the perspective of athletes in Sudan are:- The political will of the Government and political support for the process.- Provide the institutional and regulatory framework and regulatory mechanism for the privatization program.- The privatization program is part of a general program of economic reform .hm